Biogas Production from Palm Oil Mill Effluent and the Prospect of Co-digestion with Empty Fruit Bunches – A Comprehensive Review - Afid Fitro Setiawan; Agus Haryanto; Udin Hasanudin; Sugeng Triyono; Dewi Agustina Iryani (The University of Lampung, 2025)
Palm oil mill effluent (POME) and oil palm empty fruit bunches (OPEFB) represent two major waste streams in the palm oil industry that pose serious environmental challenges but also offer significant opportunities for renewable energy generation. This review comprehensively discusses the development of biogas production from POME through anaerobic digestion (AD) and explores the prospects of co-digestion with OPEFB to improve system efficiency and sustainability. A systematic literature survey of over 150 publications from the past four decades was conducted to evaluate technological evolution, operational parameters, methane yield, and environmental implications. The review identifies five major phases of POME biogas development—from early feasibility studies in the 1980s to the current exploitation phase integrating energy recovery, carbon credit schemes, and circular bioeconomy principles. Anaerobic digestion of POME in covered lagoon systems has achieved COD removal efficiencies exceeding 90% and methane yields of 0.28–0.34 Nm³ CH₄ per kg COD removed, supporting electricity generation potentials above 1 GW nationwide. Meanwhile, co-digestion with OPEFB enhances process stability, optimizes the C/N ratio, and improves methane production by 20–40% depending on substrate ratio and pretreatment. The integration of POME–OPEFB co-digestion can substantially reduce greenhouse gas emissions and provide value-added biofertilizers, thereby strengthening the environmental and economic sustainability of palm oil mills. Despite technological advances, several challenges remain, including high investment cost, OPEFB pretreatment, and limited policy support for grid connection. Further development of scalable, low-cost digesters and biogas upgrading systems is essential to realize the full potential of biogas as a renewable energy pathway within the palm oil sector.